MANAJEMEN PEMBELAJARAN AL-QUR’AN DALAM PEMBENTUKAN KARAKTER RELIGIUS PESERTA DIDIK (STUDI KASUS DI SD IT LAN TABUR OKU TIMUR) - Riduwan Rifa’i; Susilo; Anti Nanda Mita; Siti Kasilatun Mukrodah; Imron Rosyadi (STKIP Subang, 2026)
This study aims to analyse the planning, implementation, and evaluation of Al-Qur'an learning in shaping the religious character of students at SD IT Lan Tabur OKU Timur. The study uses a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation, then analysed using Miles and Huberman's interactive model with data validity maintained through triangulation and member checks. The results showed that Al-Qur'an learning was managed in a planned, integrated, and sustainable manner through synergy between planning, implementation, and evaluation of learning. Planning is strategically formulated by integrating academic targets and religious values, learning implementation is carried out adaptively through a variety of methods tailored to the abilities and characteristics of students and supported by teacher role models and a religious school culture, while evaluation is carried out comprehensively covering cognitive, psychomotor, and affective aspects. The management of Al-Qur'an learning contributes significantly to improving the discipline, obedience, and worship habits of students, so that Al-Qur'an learning functions effectively as a means of shaping religious character in schools.